Assessing economic feasibility of bio-energy feedstock cultivation on marginal lands. (November 2021) - Patel, Beena; Patel, Akash; Syed, Bakhtiyar Alam; Gami, Bharat; Patel, Pankaj
Abstract: Second generation biofuel needs lignocellulosic biomass cultivated on marginal wasteland that does not conflict with food crops for land and should be long-term economically viable. Therefore, high biomass yielding varieties of sorghum ( Sorghum bicolor (L.) Moench), pearl millet ( Pennisetum glaucum ) and bamboo ( Bambusa balcooa ) were cultivated for 3 consecutive years in the farmers' fields of three districts of Gujarat state of India. Capital and operational costing, total revenue generation and operational profit were calculated for cultivation process. Net present value (NPV) and internal rate of return (IRR) were calculated to compare profitability. Biomass varieties of sorghum, pearl millet and bamboo showed annually 40.18 MT, 26.56 MT and 24.2 MT per hectare biomass yields with gross profit of 1804.42 USD, 293.11 USD and 3016.8 USD respectively. Gujarat state possesses 2488600 ha marginal wasteland classified as culturable waste land, current fallow land and other fallow land. If these marginal wastelands cultivate biomass sorghum and bamboo, considering 70% yield compared to farmer's field trials, then 28.13 MT dry biomass from sorghum and 16.94 MT dry biomass from bamboo can be produced annually per hectare with gross profit of 898.00 USD per ha and 1924.4 USD per ha respectively. Economic sensitivity analysis suggested that biomass yield less than 50% for sorghum and less than 30% for bamboo, as compared to the farmers' field data showed lower IRR and payback time beyond 10 years with negative NPV. A thoughtful resource and policy integration have been recommended to promote bio-energy feedstock cultivation on marginal lands in India. Highlights: Sorghum, pearl millet & bamboo showed 40.2, 26.5 and 24.2 MT ha −1 yr −1 biomass yields. Sorghum and bamboo showed 28.13 and 16.94 MT ha −1 yield on marginal land. Profit of 898 & 1924 USD ha −1 yr −1 for sorghum & bamboo, respectively noted on wastelands. Low IRR, return beyond 10 yrs & negative NPV seen for <50% sorghum & <30% bamboo yield. Annually 70 mMt sorghum or 24 mMt bamboo can be produced on 2.48 m ha marginal land.